2014
DOI: 10.1128/mcb.01121-13
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 Regulates Genomic Action of the Glucocorticoid Receptor in Neural Stem Cells

Abstract: While glucocorticoids (GCs) are used clinically to treat many conditions, their neonatal and prenatal usage is increasingly controversial due to reports of delayed adverse outcomes, especially their effects on brain development. Such alterations may reflect the impact of GCs on neural progenitor/stem cell (NPSC) function. We previously demonstrated that the lipid raft protein caveolin-1 (Cav-1) was required for rapid GC signaling in embryonic mouse NPSCs operating through plasma membranebound glucocorticoid re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 52 publications
(81 reference statements)
2
29
0
Order By: Relevance
“…We have also found that the GR non-genomic pathway in NSPCs does not act independently, but rather indirectly modulates a genomic transcriptional response 77 . To understand whether the non-genomic GC pathway contributed to genomic action, we utilized Cav-1 knockout mice, interfering with non-genomic GR signaling.…”
Section: Gc Signaling In the Developing Brainmentioning
confidence: 67%
See 2 more Smart Citations
“…We have also found that the GR non-genomic pathway in NSPCs does not act independently, but rather indirectly modulates a genomic transcriptional response 77 . To understand whether the non-genomic GC pathway contributed to genomic action, we utilized Cav-1 knockout mice, interfering with non-genomic GR signaling.…”
Section: Gc Signaling In the Developing Brainmentioning
confidence: 67%
“…Our results demonstrated that non-genomic action of lipid-raft associated GR was required for efficient phosphorylation of GR at a specific site, Serine 211. Furthermore, the GR transcriptome was altered in Cav-1 knockout mice, further suggesting that transcriptional output may be altered by Cav-1 interactions 77 . Site-specific phosphorylation of GR at serine 211 may contribute to differential transcriptional outcomes of sGC exposure of NSPCs as evidenced by the differential recruitment of phosphorylated GR to select target genes of wild type versus Cav-1 knockout mouse NSPCs.…”
Section: Gc Signaling In the Developing Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…It therefore readily engages ERα bound to caveolin-1, which serves as a scaffold for membrane-localized signalling molecules. Similarly, GR has been noted to localize to lipid rafts in association with caveolin-1 in neural progenitor and/or stem cells 64 . As noted above, classic VDR can also be found at caveolae 38 .…”
Section: Receptor Trafficking To the Membranementioning
confidence: 96%
“…At present, the exact pathological mechanism underlying SANFH is not fully known; however, numerous studies have indicated that a reduced number and the weakened activity of MSCs in the femoral neck and proximal femur may be among the underlying causes of SANFH (22)(23)(24). Due to the reduction in the number or the activity level of MSCs, their osteogenetic capacity decreases, and the lesion of necrotic bone cannot be effectively repaired, leading to the collapse of the femoral head (25). In the present study, following the routine culture of MSCs for 3 weeks, the number of adipocytes was found to be clearly detectable in the MSCs of the SANFH group compared with control and TANFH groups.…”
Section: Discussionmentioning
confidence: 99%